The origin of hydrous, high-δ18O voluminous volcanism: diverse oxygen isotope values and high magmatic water contents within the volcanic record of Klyuchevskoy volcano, Kamchatka, Russia - Auer Sara; Bindeman Ilya; Wallace Paul; Ponomareva Vera; Portnyagin Maxim (My University, 2009)
Klyuchevskoy volcano, in Kamchatka’s subduction zone, is one of the most active arc volcanoes in the world and contains some of the highest δ18O values for olivines and basalts. We present an oxygen isotope and melt inclusion study of olivine phenocrysts in conjunction with major and trace element analyses of 14C- and tephrochronologically-dated tephra layers and lavas spanning the eruptive history of Klyuchevskoy. Whole-rock and groundmass analyses of tephra layers and lava samples demonstrate that both high-Mg (7–12.5 wt% MgO) and high-Al (17–19 wt% Al2O3, 3–6.5 wt% MgO) basalt and basaltic andesite erupted coevally from the central vent and flank cones. Individual and bulk olivine δ18O range from normal MORB values of 5.1‰ to values as high as 7.6‰. Likewise, tephra and lava matrix glass have high-δ18O values of 5.8–8.1‰. High-Al basalts dominate volumetrically in Klyuchevskoy’s volcanic record and are mostly high in δ18O. High-δ18O olivines and more normal-δ18O olivines occur in both high-Mg and high-Al samples. Most olivines in either high-Al or high-Mg basalts are not in oxygen isotopic equilibrium with their host glasses, and Δ18Oolivine–glass values are out of equilibrium by up to 1.5‰. Olivines are also out of Fe–Mg equilibrium with the host glasses, but to a lesser extent. Water concentrations in olivine-hosted melt inclusions from five tephra samples range from 0.4 to 7.1 wt%. Melt inclusion CO2 concentrations vary from below detection (<50 ppm) to 1,900 ppm. These values indicate depths of crystallization up to ~17 km (5 kbar). The variable H2O and CO2 concentrations likely reflect crystallization of olivine and entrapment of inclusions in ascending and degassing magma. Oxygen isotope and Fe–Mg disequilibria together with melt inclusion data indicate that olivine was mixed and recycled between high-Al and high-Mg basaltic melts and cumulates, and Fe–Mg and δ18O re-equilibration processes were incomplete. Major and trace elements in the variably high-δ18O olivines suggest a peridotite source for the parental magmas. Voluminous, highest in the world with respect to δ18O, and hydrous basic volcanism in Klyuchevskoy and other Central Kamchatka depression volcanoes is explained by a model in which the ascending primitive melts that resulted from the hydrous melt fluxing of mantle wedge peridotite, interacted with the shallow high-δ18O lithospheric mantle that had been extensively hydrated during earlier times when it was part of the Kamchatka forearc. Following accretion of the Eastern Peninsula terrains several million years ago, a trench jump eastward caused the old forearc mantle to be beneath the presently active arc. Variable interaction of ascending flux-melting-derived melts with this older, high-δ18O lithospheric mantle has produced mafic parental magmas with a spectrum of δ18O values. Differentiation of the higher δ18O parental magmas has created the volumetrically dominant high-Al basalt series. Both basalt types incessantly rise and mix between themselves and with variable in δ18O cumulates within dynamic Klyuchevskoy magma plumbing system, causing biannual eruptions and heterogeneous magma products.
Keywords: 38.29.15 Геохронология по данным абсолютного возраста; 38.37.25 Вулканология; Ключевской